Co(iii) complexes of (1, 3-selenazol-2-yl)hydrazones and their sulphur analogues. Issue 9 (15th February 2017) - Filipović, Nenad R.; Elshaflu, Hana; Grubišić, Sonja; Jovanović, Ljiljana S.; Rodić, Marko; Novaković, Irena; Malešević, Aleksandar; Djordjević, Ivana S.; Li, Haidong; Šojić, Nešo; Marinković, Aleksandar; Todorović, Tamara R.
Abstract : Se-based complexes showed potent biological activity and lower toxicity in comparison to their sulphur analogues. Abstract : The first Co(iii ) complexes with (1, 3-selenazol-2-yl)hydrazones as an unexplored class of ligands were prepared and characterized by NMR spectroscopy and X-ray diffraction analysis. The novel ligands act as NNN tridentate chelators forming octahedral Co(iii ) complexes. The impact of structural changes on ligands' periphery as well as that of isosteric replacement of sulphur with selenium on the electrochemical and electronic absorption features of complexes are explored. To support the experimental data, density functional theory (DFT) calculations were also conducted. Theoretical NMR chemical shifts, the relative energies and natural bond orbital (NBO) analysis are calculated within the DFT approach, while the singlet excited state energies and HOMO–LUMO energy gap were calculated with time-dependent density functional theory (TD-DFT). The electrophilic f − and nucleophilic f + Fukui functions are well adapted to find the electrophile and nucleophile centres in the molecules. Both (1, 3-selenazol-2-yl)- and (1, 3-thiazol-2-yl)hydrazone Co(iii ) complexes showed potent antimicrobial and antioxidant activity. A significant difference among them was a smaller cytotoxicity of selenium compounds.